Regulating Banks The Politics of Instability. - Whitworth, Andrew (Finance Matters., 2021)
Far from creating stability, argues Andrew Whitworth, the regulatory impulse of policy-makers since the financial crisis has inevitably led to greater instability in the banking sector and fails to avoid future boom and bust cycles.